2021
DOI: 10.1155/2021/6630715
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin Increases the Frequency of Follicular T Helper Cells with Enhanced IL21 Secretion and OX40 Expression in Lupus-Prone MRL/lpr Mice

Abstract: Systemic lupus erythematosus is characterized by high levels of IgG class autoantibodies that contribute to the pathophysiology of the disease. The formation of these autoantibodies occurs in the germinal centers, where there is cooperation between follicular T helper cells (TFH) and autoreactive B cells. Prolactin has been reported to exacerbate the clinical manifestations of lupus by increasing autoantibody concentrations. The objective of this study was to characterize the participation of prolactin in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…PRL does not seem to affect the formation of mature FO and MZ B cells, since we did not find differences in the absolute numbers of these populations ( 16 ). However, in T cells PRL increases the expression of CD25 and CD69 (activation molecules) on T cells ( 40 , 41 ), and of OX40 on follicular T cells ( 42 ). We did not observe an effect of PRL on the expression of the B-cell activation markers CD80 and CD86.…”
Section: Discussionmentioning
confidence: 99%
“…PRL does not seem to affect the formation of mature FO and MZ B cells, since we did not find differences in the absolute numbers of these populations ( 16 ). However, in T cells PRL increases the expression of CD25 and CD69 (activation molecules) on T cells ( 40 , 41 ), and of OX40 on follicular T cells ( 42 ). We did not observe an effect of PRL on the expression of the B-cell activation markers CD80 and CD86.…”
Section: Discussionmentioning
confidence: 99%
“…have reported that PRL increased the number and activation of IL21-producing OX40+ Tfh cells. These cells promoted the formation of GCs, interfered with tolerance induction, and facilitated the generation of autoreactive plasma cells, with the consequent autoantibody secretion ( 52 ). In SLE patients, a higher percentage of CD4+ OX40+ T cells has also been shown to indicate increased disease activity ( 53 ) ( Figure 1 ).…”
Section: Prolactin and Sle: Adaptive Immune Response Cellsmentioning
confidence: 99%
“…En nuestro grupo de trabajo, se ha tratado de comprender el papel de la PRL en el desarrollo del LES utilizando ratones MRL/lpr. Se ha demostrado de manera ex vivo que los linfocitos B-GC y Tfh expresan la isoforma larga del R-PRL tanto en las cepas que desarrollan LES como en la cepa control (C57BL/6) (Alemán-García et al, 2021;Carreon, 2019). En los linfocitos Tfh de los ratones que desarrollan LES la expresión del receptor es mayor e incrementa conforme a la edad, presentando un patrón diferente con respecto a la cepa control.…”
Section: Antecedentes Prolactina Y Lupus Eritematoso Sistémicounclassified
“…En los linfocitos Tfh de los ratones que desarrollan LES la expresión del receptor es mayor e incrementa conforme a la edad, presentando un patrón diferente con respecto a la cepa control. (Alemán-García et al, 2021).…”
Section: Antecedentes Prolactina Y Lupus Eritematoso Sistémicounclassified